Morphology of House Pattern in Tenganan Dauh Tukad Village, Karangasem - Acwin Dwijendra, Ngakan Ketut (Udayana Journal of Social Sciences and Humanities; Vol 5 No 1 (2021): UJoSSH, February 2021DO - 10.24843/UJoSSH.2021.v05.i01.p06, 2021)
Traditional Settlements Tenganan Dauh Tukad Traditional Village, Karangasem regency, has a uniqueness of traditional dwelling patterns that become a local character of the region. However, along with the development of tourism in this village, the traditional settlement is not only a pride, but also the object of commodification. This is an interesting phenomenon where on the one hand, people try to maintain their traditional residential identity to attract tourists visiting, but, on the other hand, they change their dwelling as a tourism facility. The change is a challenge and a pressure for maintaining the traditional configuration as an identity. This is a phenomenon of conflict in the development of a cultural tourism area. On the one hand, tourists expect a natural and original nature and culture. On the other hand, society and culture change as the society interacts with the outside culture and the desire to accommodate the needs of the visiting tourists. Therefore, the purpose of this study was to investigate the paradoxical phenomenon of changes in the morphology of residential patterns in Tenganan Dauh Tukad Village and explore the conflict between conservation of traditional housing character and tourism demand. By conducting field studies (measurements), of selected stratified random sampling houses, and interviews, to examine the impact of changes on values ??and their meanings, this study will discuss changes in the physical configuration, meanings, and values ??of a traditional house. This research will explore the original roles and meanings of altered housing that can still be maintained and the new roles and values ??contained in the new configuration. In this study will also discuss the impact of new values ??on the meaning and value of the original configuration. With the identification of the morphologic character of the residential pattern, it is expected to be a model of change and provide an appropriate perspective for the community, the government and the tourism actors in transforming the traditional housing in Tenganan Dauh Tukad Village, Karangasem Regency.